122 INTRAUTERINE GROWTH RESTRICTION AFFECTS INSULIN GROWTH FACTOR BINDING PROTEIN 3 BUT NOT INSULIN-LIKE GROWTH FACTOR 1 RECEPTOR EXPRESSION IN THE DEVELOPING RAT LUNG. Issue 1 (1st January 2007) - Langen, R. F.; Callaway, C. W.; McKnight, R. A.; Yu, X.; Lane, R. H.
Abstract : Background: Intrauterine growth restriction (IUGR) predisposes neonates toward chronic lung changes characterized by mesenchymal thickening. Insulin-like growth factor 1 (IGF-1) plays a crucial role in normal lung growth and development. Key modulators of IGF-1 activity include IGFBP-3 and IGF-1r. Previous studies have shown that IGFBP-3 binds IGF-1 and decreases its activity. In addition, evidence suggests that IGFBP-3 may exhibit growth inhibitory effects independent of its ability to down-regulate IGF-1 activity. Specifically, IGFBP-3 has been shown to inhibit the growth of fibroblasts derived from IGF-1r knockout mice. IGF-1r is a tyrosine kinase receptor that mediates the effects of IGF-1. Objective: We hypothesized that IUGR would decrease IGFBP-3 expression in the developing rat lung and thereby contribute to increased IGF-1 activity and mesenchymal thickening. Furthermore, we hypothesized that these changes would be independent of IGF-1r expression. Design/Methods: To prove these hypotheses, we used a rat model of IUGR induced through uteroplacental insufficiency. Lungs of control and IUGR rats ( n = 6-8 litters per group) at day 0 and day 21 were harvested and flash frozen. We measured relative mRNA levels of IGFBP-3 and IGF-1r with RT-PCR at day 0 and day 21. We also measured IGFBP-3 protein levels in day 0 rats. Results: Significant results are expressed as percent of control ± SEM. IGF-1r mRNA levels were not different between IUGR and control rat lungs at either day 0 ( p = .66) or day 21 ( p = .32). While IGFBP-3 mRNA and protein levels did not differ at day 0 ( p = .81 and .90, respectively), mRNA levels differed significantly by day 21 (40.1% ± 7.0%, p = .05). Conclusions: We conclude that IUGR decreases IGFBP-3 mRNA levels in the postnatal rat lung. IGF-1r expression is unaffected by IUGR. These results are particularly intriguing because although IUGR leads to mesenchymal thickening in the day 21 rat lung, we have previously demonstrated that IGF-1 mRNA expression in the postnatal IUGR rat lung is unchanged. We speculate that decreased IGFBP-3 during alveolarization results in increased IGF-1 bioavailability, which contributes to the mesenchymal thickening seen in the postnatal IUGR rat lung. This may be secondary to IUGR-induced imprinting on the IGFBP-3 gene that subsequently decreases its expression. Supported by the CHRC.